(3MGTjI TQM GdeWdY GdSYjO ddTQja GdLQLGfjs - (3eLghds ((3EHQGgje GdCTahOQhjs)
(3ChdgG (B:s
(3HSe Gddg bGd aQjO YUQg JZeOg Gddg HZaQGfg GdMeO ddg hGdajV aj GdGUWdGM EfeG ojWdb Ydi Yd jaYdg OGFeG dG dYhV hdG dZQV hefg bhdge GdeHOC GdajGV s
(3BNQgG (B:s
(3hajg eG YQaJ Ydi eG PcQg ef Cf GdYGe EfeG jchf CYQa Ch CcKQ hLhOG aj GdYbd EPG cGf PGJjG ddNGb GdeUhQ HGdcfg hGdLfS djS PGJjG ddaUd ceG eQ hbO jbGd GdYGe CcKQ Jes
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdadSaI hGdefWbs